(untitled) (Revista Lusófona de Educação, 2026)
The Bologna Process has led to changes in teaching policies and practices, emphasising the need to innovate teaching. Although pedagogical innovation can be developed in different ways, it is argued that it should favour change in institutional cultures, reinforcing the status of teaching through self-study and the development of a culture of scholarship of teaching and learning (SoTL). Considering the scarcity of research on innovative practices in higher education in Portugal, the descriptive study presented here focused on the analysis of 167 reports of pedagogical experiences published between 2019 and 2023 in the proceedings of the National Congress on Pedagogical Practices in Higher Education, aiming to characterise the contexts of the experiences, the pedagogical approaches explored and the impact assessment processes. The results highlight the contextual and methodological diversity in the development of student-centred practices, identifying their potential and shortcomings. Although the experiences reported constitute self-study practices and are close to the notion of SoTL, they are not conceptualised in this way and the role of innovation in professional teaching development and the transformation of institutional cultures is rarely discussed. The study highlights the importance of diversity as an intrinsic dimension of change, but also the need to create conditions that support and value SoTL in institutions.